2022
DOI: 10.1038/s41467-022-30167-0
|View full text |Cite
|
Sign up to set email alerts
|

Calcium bursts allow rapid reorganization of EFhD2/Swip-1 cross-linked actin networks in epithelial wound closure

Abstract: Changes in cell morphology require the dynamic remodeling of the actin cytoskeleton. Calcium fluxes have been suggested as an important signal to rapidly relay information to the actin cytoskeleton, but the underlying mechanisms remain poorly understood. Here, we identify the EF-hand domain containing protein EFhD2/Swip-1 as a conserved lamellipodial protein strongly upregulated in Drosophila macrophages at the onset of metamorphosis when macrophage behavior shifts from quiescent to migratory state. Loss- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 79 publications
1
22
0
Order By: Relevance
“…Recent studies further revealed that the function chitinases are not exclusive to catalyze the hydrolysis of chitin producing pathogens, but also include a crucial role in bacterial infections and inflammatory diseases 54 . Interestingly our GO-term analysis not only identified the enrichment of genes involved in innate immune response but also an increased expression of genes implicated in cell-cell adhesion and septate junction assembly (Figure 3H), a special feature that we could already observe in our previous bulk RNA seq analysis of pupal hemocytes (Supplementary figure S2M, 29 . Septate junction (SJ) proteins play an essential role in regulating hematopoiesis in the Drosophila lymph gland, but might be also essential for an effective response to parasitic wasp attack 55 56 .…”
Section: Resultssupporting
confidence: 60%
See 4 more Smart Citations
“…Recent studies further revealed that the function chitinases are not exclusive to catalyze the hydrolysis of chitin producing pathogens, but also include a crucial role in bacterial infections and inflammatory diseases 54 . Interestingly our GO-term analysis not only identified the enrichment of genes involved in innate immune response but also an increased expression of genes implicated in cell-cell adhesion and septate junction assembly (Figure 3H), a special feature that we could already observe in our previous bulk RNA seq analysis of pupal hemocytes (Supplementary figure S2M, 29 . Septate junction (SJ) proteins play an essential role in regulating hematopoiesis in the Drosophila lymph gland, but might be also essential for an effective response to parasitic wasp attack 55 56 .…”
Section: Resultssupporting
confidence: 60%
“…As previously reported 6466 , prominent kn expression is initially found in dorsal muscle fields in the thoracic and abdominal segments of early pupae (Figure 7A), and its expression becomes restricted to segmental abdominal muscles, along the anterior-posterior border of the developing wing and in pericardial cells along the dorsal vessel in later pupal development (>16h APF-96h APF; Figure 7B, C). High-resolution spinning disc live cell imaging microscopy of 4h APF old pupae revealed migrating single kn -marked PSC cells that form polarized dynamic lamellipodial protrusions and start to redistribute from the dorsal patches of the body wall as similarly observed for plasmatocytes (Figure 7D; Supplementary movie M1) 9, 29 . kn -marked PSC cells are highly motile but much smaller as compared to hml -marked plasmatocytes, confirming that we indeed observed PSCs when focusing on small kn positive cells instead of plasmatocytes (Supplementary movies M1 and M2).…”
Section: Resultsmentioning
confidence: 65%
See 3 more Smart Citations